Application of silicon and biochar alleviates the adversities of arsenic stress in maize by triggering the morpho-physiological and antioxidant defense mechanisms - Sattar, Abdul; Sher, Ahmad; Abourehab, Mohammed A. S.; Ijaz, Muhammad; Nawaz, Muhammad; Ul-Allah, Sami; Abbas, Tahira; Shah, Adnan Noor; Imam, Mohamed S.; Abdelsalam, Nader R.; Hasan, Mohamed E.; Abbas, Aown; et al. (Frontiers in Environmental Science, 2022)
Arsenic (As) contamination in the soil adversely affects crop productivity, grain quality, and human health. A pot experiment was performed to assess the sole and combined effects of Si and biochar on growth, physiological and antioxidant defense mechanisms, yield, and grain quality of maize. Soil treatments comprised of control (no treatment), As, Si, biochar, Si + biochar, As + Si, As + biochar, and As + Si + biochar placed in a completely randomized design with three replications. As toxicity significantly reduced chlorophyll a (5.18%), chlorophyll b (33.87%), chlorophyll a + b (11.67%), and primary metabolites [soluble protein (54.93%), amino acids (24.85%), total soluble sugars (39.77%), and phenolic contents (25.88%)], while increasing the activities of enzymatic antioxidants such as superoxide dismutase (SOD) by 43.51%, peroxidase (POD) by 47.93%, catalase (CAT) by 47.98%, and ascorbate peroxidase (APX) by 59.02%, as well as that of lipid peroxidation in the leaves of maize. In addition, As contamination reduced the grain yield and yield-related attributes relative to the respective controls. Among the soil applications, the interactive effect of Si and biochar improved maize grain yield (12.12%) by triggering activities of enzymatic antioxidants and proline contents and reducing the H2O2 and MDA contents. The combined application of Si and biochar enhanced the Si contents in shoots of the control and As-contaminated plants, while significantly reducing As concentration in shoots (69%) and grains (142%). In conclusion, the combined application of Si and biochar was found to be a fruitful soil amendment strategy to improve the yield of maize and reduce the toxic limit of As under As-contaminated soil. The results of this study may be useful for the cultivation of food crops under AS-contaminated soils, but before commercial recommendation, more trails are required under field conditions.